PCNA directs type 2 RNase H activity on DNA replication and repair substrates. - Bubeck, D; Reijns, M; Graham, S; Astell, K; Jones, E; Jackson, A (2011)
Ribonuclease H2 is the major nuclear enzyme degrading cellular RNA/DNA hybrids in eukaryotes and the sole nuclease known to be able to hydrolyze ribonucleotides misincorporated during genomic replication. Mutation in RNASEH2 causes Aicardi-Goutières syndrome, an auto-inflammatory disorder that may arise from nucleic acid byproducts generated during DNA replication. Here, we report the crystal structures of Archaeoglobus fulgidus RNase HII in complex with PCNA, and human PCNA bound to a C-terminal peptide of RNASEH2B. In the archaeal structure, three binding modes are observed as the enzyme rotates about a flexible hinge while anchored to PCNA by its PIP-box motif. PCNA binding promotes RNase HII activity in a hinge-dependent manner. It enhances both cleavage of ribonucleotides misincorporated in DNA duplexes, and the comprehensive hydrolysis of RNA primers formed during Okazaki fragment maturation. In addition, PCNA imposes strand specificity on enzyme function, and by localizing RNase H2 and not RNase H1 to nuclear replication foci in vivo it ensures that RNase H2 is the dominant RNase H activity during nuclear replication. Our findings provide insights into how type 2 RNase H activity is directed during genome replication and repair, and suggest a mechanism by which RNase H2 may suppress generation of immunostimulatory nucleic acids.